2015
DOI: 10.1016/j.eatbeh.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Episodic future thinking reduces delay discounting and energy intake in children

Abstract: Discounting of larger future rewards in favor of smaller immediate rewards is known as delay discounting. High delay discounting or a bias towards immediate gratification impedes self-regulation and is associated with maladaptive eating behaviors. Children in general show greater delay discounting than adults. Obese children in particular, have greater difficulty delaying gratification for edible rewards. Episodic future thinking (EFT) which is mental self-projection to pre-experience future events reduces del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
167
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 54 publications
(76 reference statements)
17
167
1
Order By: Relevance
“…Excessive discounting of delayed rewards is posited as a trans-disease process in which many different types of behavioral maladies, including overeating and drug addiction, exhibit excessive undervaluation of future rewards (Bickel et al, 2012b). Importantly, EFT decreased delay discounting in overweight and obese adults as well as 9- to 14-year-old obese adolescents (Daniel et al, 2013a,b, 2015), consistent with our results in alcohol-dependent individuals. Our results also revealed a decrease in initial consumption in hypothetical alcoholic drinks during a purchase task following EFT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Excessive discounting of delayed rewards is posited as a trans-disease process in which many different types of behavioral maladies, including overeating and drug addiction, exhibit excessive undervaluation of future rewards (Bickel et al, 2012b). Importantly, EFT decreased delay discounting in overweight and obese adults as well as 9- to 14-year-old obese adolescents (Daniel et al, 2013a,b, 2015), consistent with our results in alcohol-dependent individuals. Our results also revealed a decrease in initial consumption in hypothetical alcoholic drinks during a purchase task following EFT.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, when alcoholic drinks were free or at very low cost, EFT participants purchased less than the control group. These data are again consistent with data from Daniel and colleagues (2013b, 2015) in which EFT decreased caloric intake in overweight adults and 9- to 14-year-old obese adolescents when given free access to highly palatable foods. These data, in combination, suggest that EFT disrupts excessive discounting of delayed rewards, overvaluation of immediate rewards, and supports the hypothesis that EFT may hold future implications for manipulating valuation of future rewards in multiple therapeutic arenas.…”
Section: Discussionsupporting
confidence: 89%
“…EFT participants generated episodic future events similar to those used in previous EFT study procedures (Daniel & Epstein, 2013; Daniel et al, 2015; Daniel et al, 2013). Participants in the EFT condition generated personalized future events that they were looking forward to and could vividly imagine for three different future time periods.…”
Section: Methodsmentioning
confidence: 99%
“…One way to shift temporal perspective so that people are more likely to choose a larger, but delayed reward, is to engage in episodic future thinking (EFT) (Daniel, Said, Stanton, & Epstein, 2015; Daniel, Stanton, & Epstein, 2013a, 2013b; Lin & Epstein, 2014; Peters & Buchel, 2010). EFT is a skill that allows us to use mental simulation to place ourselves in the future and pre-experience an event (Atance & O'Neill, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown EFT effectively reduces DD in individuals that are typically high in DD (Daniel et al, 2013a), and that EFT reduces excessive energy intake in obese adults and children as well (Daniel et al, 2015; Daniel et al, 2013b). In these experiments, personalized audio EFT cues that were played during an ad libitum eating task significantly reduced the amount of calories consumed by subjects compared to episodic thinking control conditions.…”
Section: Introductionmentioning
confidence: 99%